the Suspension and the conditions for its implementation in the laws of criminal procedures and its impact on personal freedom (a comparative study) - Ameera Abdul Jabbar Ali, Researcher; Zainab Ahmed, Assist prof .Dr (lark, 2023)
The present paper deals with the police power to stop persons under criminal legislations. A police officer & members of law enforcement officials have powers to stop and question anyone in the street or public places. This research showed that Using the power to stop by mentioned authorities can only apply when there is a belief on reasonable grounds that a stopped person acting suspiciously or there are reliable information, facts to suspect that person has committed a crime. It has been shown that the enforcement of such authority should be for the purpose of combating crimes and to maintain public interest. What follows is that the police officer while conducting power to stop persons should use special criminal procedural measures with respecting fundamental liberties & legal rights of individuals. The paper has been divided into sections. Finally, it has been concluded that the special procedures should be flowed during conducting police power to arrest with respecting the right and liberties of individuals and guarantees of the right to personal privacy.